The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1177/073168449901801005
|View full text |Cite
|
Sign up to set email alerts
|

Laser Transmission Welding of Thermoplastics: Analysis of the Heating Phase

Abstract: In laser transmission welding, the parts to be joined are brought into contact prior to welding, and the heating and joining phase take place simultaneously. The laser beam of the Nd:YAG laser penetrates the transparent part being joined and is converted into heat by the absorbing part. The transparent part is similarly heated and plasticised by means of heat conduction, thereby ensuring that the parts are welded together. When the heating phase was analysed, it was seen that if the part that absorbs the lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The scattering of the laser beam is an important phenomenon because it has a great influence on the energy distribution within the materials, especially at the interface where the heat source has to be defined. An experimental solution to this necessity was given by Potente and Becker [4,6] which measured the laser beam profile before and after the transparent component, thus obtaining both the attenuation and the energy distribution at the interface. Within the present study, the scattering of the laser beam in semitransparent low absorbent polymers is modeled combining Mie theory and the Monte Carlo method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scattering of the laser beam is an important phenomenon because it has a great influence on the energy distribution within the materials, especially at the interface where the heat source has to be defined. An experimental solution to this necessity was given by Potente and Becker [4,6] which measured the laser beam profile before and after the transparent component, thus obtaining both the attenuation and the energy distribution at the interface. Within the present study, the scattering of the laser beam in semitransparent low absorbent polymers is modeled combining Mie theory and the Monte Carlo method.…”
Section: Introductionmentioning
confidence: 99%
“…In computing the temperature field within the materials and at the interface, the heat conduction equation is used [3][4][5][6][7] taking in account a perfect contact between the two components subjected to welding. An estimation of the temperature at the interface is required for establishing the welding process parameters like laser power and welding speed.…”
Section: Introductionmentioning
confidence: 99%
“…LTW is a 3-D [28][29][30][31][32] heat transfer problem. However, some authors have shown that 1-D [33,34] and 2-D [29,13,35] thermal models can be used to obtain reasonable estimations of the temperature distributions. In most cases, the simplicity and low computational times associated with 1-and 2-D timedependent models are traded-off against the accuracy associated with 3-D time-dependent solutions.…”
Section: Ltw Modellingmentioning
confidence: 99%
“…To simulate the temperature distribution, the heat conduction equation is solved, which has been done for laser-transmission welding of polymers for many years [28][29][30][31][32][33][34]. The heat conduction equation is given in the following form…”
Section: Simulation Of Temperature Fieldmentioning
confidence: 99%